Differentiëren in Nederlandse taallessen : een praktijkvoorbeeld - Debrabandere, Mieke; Baert, Elianne; Lamote, Johan; Verbruggen, Katrien; Tavernier, Veerle (Gent: De Poort-Beraber)
"Werkgroep methodiek: Mieke Debrabandere, Elianne Baert, Johan Lamote, Katrien Verbruggen, Veerle Tavernier"